2015
DOI: 10.1007/s00373-015-1579-5
|View full text |Cite
|
Sign up to set email alerts
|

Network Decontamination with a Single Agent

Abstract: Faults and viruses often spread in networked environments by propa-10 gating from site to neighboring site. We model this process of network contamina-11 tion by graphs. Consider a graph G = (V, E), whose vertex set is contaminated 12 and our goal is to decontaminate the set V (G) using mobile decontamination 13 agents that traverse along the edge set of G. Temporal immunity τ (G) ≥ 0 is 14 defined as the time that a decontaminated vertex of G can remain continuously 15 exposed to some contaminated neighbor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Monotonicity is assumed in [7,13,12,14] that a node cleaned by the agent will not get affected again. Non-monotonic strategies are given in [10]. Some other problems related to graph immunization include the influence maximization [21], the filter placement [11] and the critical node detection problem (CNDP) [5,20,35].…”
Section: Related Workmentioning
confidence: 99%
“…Monotonicity is assumed in [7,13,12,14] that a node cleaned by the agent will not get affected again. Non-monotonic strategies are given in [10]. Some other problems related to graph immunization include the influence maximization [21], the filter placement [11] and the critical node detection problem (CNDP) [5,20,35].…”
Section: Related Workmentioning
confidence: 99%
“…In the case of strong grids, k searchers are sufficient to clear them when the immunity is ≥ 2(2n−1) k [DFZ10]. Finally, ι 1 (G) has been studied in several classes of graphs [DJS16] such as paths: ι 1 (P n ) = 0 for every n; cycles: ι 1 (C n ) = 2 for every n, and goes to n − 1 if monotonicity is required; complete graphs: ι 1 (K n ) = n − 1 for every n; complete bipartite graphs: ι 1 (K n,m ) = 2m−1 for 3 ≤ m ≤ n; n-node trees: ι 1 (T ) ≤ 30 √ n; p × q grids: p/2 ≤ ι 1 ≤ p for p ≤ q, etc. It can be shown that there are n-node trees T for which ι 1 (T ) = Ω(n 1/3+ ) for some constant > 0 [DJS16] and a challenge would be to close the gap with the upper bound 30 √ n. The question of general planar graphs is also open.…”
Section: Recontamination Alternativesmentioning
confidence: 99%
“…once a node is decontaminated then it cannot get contaminated again (Bienstock 1991), (Flocchini 2008), (Flocchini 2007), (Fraigniaud 2008). But non-monotonic strategies are also studied (Daadaa 2016).…”
Section: Related Workmentioning
confidence: 99%